FORGING DIGITAL BUSINESS TRUST: ETHICAL STRATEGIES FOR SUSTAINABLE BUSINESS - Qona'ah El Hasan; Adi Muhamad Muhsidi; Wachjuni; Dewi Sintya (INDONESIAN JOURNAL OF BUSINESS AND ECONOMICS, 2025)
The rapid evolution of the digital landscape has positioned digital business trust as paramount for fostering sustainable relationships between businesses and stakeholders. Despite its clear benefits, including potential annual growth exceeding 10%, companies frequently encounter ethical dilemmas in data management and digital technology adoption, such as AI bias and non-transparent marketing. While transparent and ethical practices are known to enhance consumer trust, a significant gap remains in research specifically outlining comprehensive strategies for building long-term digital trust using robust systematic literature review (SLR) methodologies. This study addresses this gap by conducting an SLR to identify and analyze digital business ethics strategies contributing to trust and business sustainability. Employing Publish or Perish with Google Scholar, the search utilized keywords like "digital business ethics strategies" and "digital trust and ethics in business" for articles published between 2020 and 2025. After rigorous screening, 27 relevant articles were selected for in-depth analysis. The findings reveal that digital business trust is cultivated through multifaceted and integrated ethical strategies. These encompass the reinforcement of fundamental moral principles and awareness, stringent data transparency and accountability, adoption of stakeholder-centric approaches, seamless integration of ethics into core business models and innovation, proactive regulatory compliance, diligent ethical application in digital marketing, and the cultivation of a strong ethical leadership and organizational culture. Ultimately, this research confirms that ethics is not merely a compliance obligation but a vital strategic asset, indispensable for safeguarding long-term stakeholder relationships and ensuring sustainable business operations in the dynamic digital marketplace.